Peningkatan Pembelajaran Pesawat Sederhana dengan menggunakan Pendekatan Kontekstual di Kelas V SDN. 09 Silaut Kecamatan Silaut Kabupaten Pesisir Selatan - Jial Jial (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
This research originated from the fact in elementary school that learning is often dominated by teachers as a source of information. The main problem in this research is the achievement of learning result of class V students in science learning, which is the delivery of theory so that the concept of the material is still poorly understood by the students. The purpose of this research is to describe the improvement of science learning through contextual approach in class V. The approach used in this research is a qualitative approach with the type of research is classroom action research. The study consists of two cycles consisting of planning activities, action execution, observation and reflection. The value of learning comprehension of IPA by using the contextual approach in cycle I and cycle II have increased, where students' learning mastery cycle, I with an average of 64% and in the cycle II is 92%. In addition, students have been trained to find out, test it in study groups and then communicate it to other friends. Thus it can be concluded that learning science by using a contextual approach can improve student learning outcomes of grade V SDN 09 Kecamatan Silaut.